Antimicrobial activity of Melastoma malabathricum Linn. flower and fruit crude extracts - Che Omar, Siti Nurhadis (2012)
Natural products are rich sources of antimicrobial compounds with broad spectrum and sufficiently good pharmacokinetics to be clinically useful without chemical modifications. With the increase in microbial resistance to antibiotics, there is considerable interest in investigating the antimicrobial effects of potential plant extracts as potential sources for developing natural antimicrobial agents. Melastoma malabathricum Linn. is a shrub that belongs to the family Melastomataceae and a common herbal plant used in folk medicines to treat inflamed wounds and other ailments. It is commonly found in Malaysia with beautiful pink or purple flowers and berries-like fruits rich in anthocyanins. Hence, this study was carried out with the aim to evaluate the inhibitory activities of different concentrations of the M. malabathricum Linn. flower and fruit crude extracts against a variety of microorganisms, which comprised of 12 Gram-positive bacteria, 17 Gram-negative bacteria and three fungi species using the disc diffusion method. The lowest concentrations of the extracts producing inhibition zones against the test microorganisms were used to determine their Minimum Inhibitory Concentrations (MICs) and Minimum Bactericidal Concentrations (MBCs) or Minimum Fungicidal Concentrations (MFCs). In addition, the effects of different temperatures (4°C, 25 °C and 37 °C) and pHs (4, 6, 7 and 8) on the stability of the crude extracts correlating to their growth inhibitory ability were determined for Listeria monocytogenes IMR L55 and Staphylococcus aureus IMR S244 grown in medium supplemented with the respective crude extracts at different temperatures and pHs. In vitro cytotoxicity effect of the M. malabathricum Linn. extracts on the human Chang liver and 3T3- Fibroblast cells using the MTT assay was also carried out. Overall, the Gram-positive bacteria were more susceptible to both crude extracts compared to the Gram-negative species. The results showed that both crude flower and fruit extracts exhibited strong inhibitory activities against Micrococcus luteus but had no effects on all fungi tested. The MIC values for the crude flower and fruit extracts on all the bacteria tested ranged from 12.5 to 100.0 mg/ml. While, the average MBC values were from 50.0 to 100.0 mg/ml for both extracts. L. monocytogenes IMR L55 and S.aureus IMR S244 exhibited the highest sensitivity to both crude extracts at 100 mg/ml. The crude flower extract was more effective in inhiting the growth of L. monocytogenes IMR L55 in which a reduction of 4.5 to 8.0 log CFU/ml was detected when tested at pHs 4, 6, and 7 for 4 °C, 25 °C and 37 °C. While, the crude fruit extract was more effective in reducing the growth of S.aureus IMR S244 with 4.5 to 8.0 log CFU/ml reduction at pHs 4, 6, 7 and 8 for 25 °C and 37 °C. The MTT assay showed that the crude fruit extract exhibited an IC50 of 0.70 mg/ml when tested on Chang liver cells after 48 hours of treatment compared to the crude flower extract (IC50 ≥ 1.0 mg/ml); whereas the 3T3-Fibroblast cells incubated with the flower and fruit extracts showed an IC50 of 0.40 mg/ml and 0.60 mg/ml, respectively. Overall, the results obtained in this study pinpoint that both extracts have potentials to inhibit or kill selective bacterial pathogens, with the flower extract exhibiting better antibacterial activity compared to the fruit extract. The data also suggests the possible uses of the extracts to control selective pathogens and as natural sources for the discovery of natural antibacterial agent(s) in the future.